Spatiotemporal study of evapotranspiration in the southern part of the Aras River basin - Mahnaz Saber; bromand Salahi; Abbas Mofidi (تحقیقات کاربردی علوم جغرافیایی)
In this study, the spatiotemporal variations of evapotranspiration (ET) were investigated in the southern part of the Aras River catchment. For this purpose, the ET networked data of FLDAS Noah model with horizontal resolution of 0.1 * 0.1 degree were used for a period of 38 years (2019-1982). After validating the data, the average annual ET values ​​for the region were determined first. Then the monthly and seasonal distribution of the parameter were analyzed spatially. Subsequently, ET variations and anomalies were evaluated year to year. Also, the spatial distribution of the occurrence frequency of ET was investigated by considering the absolute thresholds of 50, 80, 100 and 120 mm for the Aras basin. The results show that the annual ET in the east of the basin is higher than the west of the basin. In the seasonal scale, spring and summer have the highest ET values, respectively. In the monthly scale, Mayو June, April and March had the highest ET values, respectively. In contrast, the autumn and winter months have the lowest average ET values. Also, the whole basin during the study period has experienced three distinct periods of ET changes that in the eastern and western parts of the basin, despite the same behavior in the second and third periods, a significant difference was observed in the first period. The results also indicate the existence of positive anomalies after 2002 in the whole basin, the highest values ​​occurred in 2018 in the west of the basin. The study of the frequency of occurrence of absolute ET thresholds on the basin shows the high frequency of ET occurrence at all thresholds in the east of the basin. A study of nearly 4 decades of ET values ​​in the Aras River Basin shows an increase in ET values ​​over the last two decades over the entire basin, which can be attributed to the occurrence of global warming.